2022
DOI: 10.1002/pmic.202100222
|View full text |Cite
|
Sign up to set email alerts
|

Advances in mass spectrometry‐based footprinting of membrane proteins

Abstract: Structural biology is entering an exciting time where many new high‐resolution structures of large complexes and membrane proteins (MPs) are determined regularly. These advances have been driven by over 15 years of technological improvements, first in macromolecular crystallography, and recently in cryo‐electron microscopy. Obtaining information about MP higher order structure and interactions is also a frontier, important but challenging owing to their unique properties and the need to choose suitable deterge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 105 publications
0
6
0
Order By: Relevance
“…Similar to FPOP, X‐ray footprinting (XFMS) utilizes hydroxyl radical labeling to determine protein HOS (Bavro et al, 2015; Maleknia et al, 2001; J. Sun et al, 2022; Xu & Chance, 2007; Gupta; Guan & Chance, 2005; Takamoto & Chance, 2006). At the National Synchrotron Light Source and the Advanced Light Source, photons of 3–30 keV are produced and can interact with water to create hydroxyl radicals (see Scheme 3) (Bavro et al, 2015; Guan & Chance, 2005; Gupta et al, 2016; Maleknia et al, 2001; J.…”
Section: Methods For Studying Aggregating Proteinsmentioning
confidence: 99%
“…Similar to FPOP, X‐ray footprinting (XFMS) utilizes hydroxyl radical labeling to determine protein HOS (Bavro et al, 2015; Maleknia et al, 2001; J. Sun et al, 2022; Xu & Chance, 2007; Gupta; Guan & Chance, 2005; Takamoto & Chance, 2006). At the National Synchrotron Light Source and the Advanced Light Source, photons of 3–30 keV are produced and can interact with water to create hydroxyl radicals (see Scheme 3) (Bavro et al, 2015; Guan & Chance, 2005; Gupta et al, 2016; Maleknia et al, 2001; J.…”
Section: Methods For Studying Aggregating Proteinsmentioning
confidence: 99%
“…Recent advances have been made that greatly expand the utility of covalent labeling reagents for mapping interacting surfaces and for reporting on conformational changes in soluble proteins. , For example, new reagents have been developed that can react with aromatic sidechains within membrane proteins and on hydrophobic patches, and a handful of recently developed methods are aimed at measuring proteome-wide conformational changes. In this report, while we set out to exploit the azido radical as a simpler means of general covalent protein labeling and subsequent derivatization, the product of these experiments is also a method for covalently modifying protein with the azido radical that captures and identifies locations of noncovalent azide binding. With our method, azide may present a unique, enrichable method to add to the existing toolbox.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it appears azide behaves similarly to the covalent labeling reagent diethylpyrocarbonate (DEPC), which has been reported to modify residues found in transmembrane domains and in soluble proteins, within structured hydrophobic patches. The reactivity of DEPC with soluble proteins is destroyed when the higher-order protein structure is greatly reduced via proteolytic digestion, , and suggests DEPC can empirically identify amino acids present in structured hydrophobic protein microdomains. Underscoring the need for empirical methods to identify hydrophobic microdomains, recent computational studies have indicated that hydrophilic amino acid sidechains are as likely to be present in these hydrophobic microdomains as are the hydrophobic sidechains, confounding the prediction of such patches from the primary sequence .…”
Section: Introductionmentioning
confidence: 99%
“…MS-based footprinting is a valuable tool for studying the interactions of MPs with other molecules and their conformational changes. Some reviews discuss covalent labeling coupled with MS [ 39 ] and the fast footprinting of MPs [ 40 ]. In this review, we focus on several advanced footprinting methods coupled with MS for (i) membrane-associated proteins, (ii) extramembrane domains, and (iii) transmembrane domains, showing how methods can be developed to probe various domains of the protein.…”
Section: Chemical Footprintingmentioning
confidence: 99%